Cuerpos melenudos, olorosos y transgresores: representación del hippie colombiano en la fotografía de prensa de Medellín y Bogotá entre 1968 y 1969 - Mares Figueras, Úrsula (Folios, revista de la Facultad de Comunicaciones y Filología, 2025)
The emergence of the hippie phenomenon in Colombia raised social alarm regarding youth groups that began to adopt aesthetics, philosophies, and practices that did not correspond to the traditional values of Colombian urban societies. The national press, aligned with the Nacional Front, played a fundamental role in the construction of the hippie as a transgressive youth body that had crossed the acceptable and tolerated boundaries of the established social and moral order. We analyze some of the first photographic representations, and the journalistic discourses that woven around them, to examine the ways in which the Colombian hippie body was constructed as a form of embodied transgression and was sensorially perceived, through smell, as malodourous and unpleasant, within a framework of asymmetrical social relations influenced by power toward youth groups that broke whit imposed moral standards.